PENERAPAN DIVERSI DAN ASAS KEPENTINGAN TERBAIK BAGI ANAK DALAM SISTEM PEMIDANAAN DI WILAYAH HUKUM DELI SERDANG (Studi Penetapan Pengadilan Negeri Lubukpakam No. 8 Pid.Sus-Anak/2017/PN-LBP) - Eva Santa R Sitepu; Madiasa Ablisar; Marlina Marlina; Edy Ikhsan (Universitas Sumatera Utara, 2018)
Abstract Determination of the Lubukpakam District Court No. 8 Pid.Sus-Anak/2017/PN-Lbp is one example of the success of diversion at the court level in Lubukpakam. Diversion in the Deli Serdang jurisdiction tends to be successful at the court level compared to the level of investigation and prosecution. This is because the diversion carried out aims to maximize the best interests of the child. Keywords: children, diversity and best interest